TRANSFORMATIONAL LEADERSHIP AND ITS IMPACT ON CHARACTER DEVELOPMENT OF STUDENTS - Khairani, Majidah; Febrinal, Dian; _, Elvarisna; Sari, Rahma; _, Asmendri; Nurva, Mirda Swetherly (Jurnal Ilmu Pendidikan Ahlussunnah, 2025)
This study aims to explore the implementation of transformational leadership by the principal and teachers at MTs Muhammadiyah Tanjung Ampalu and its impact on the character development of students. Transformational leadership, which focuses on inspiration, individual attention, and setting a good example, is believed to enhance student motivation and discipline, as well as strengthen the development of students' character in accordance with Islamic values. This research employs a qualitative approach with a case study design, where data is collected through in-depth interviews and participatory observations of the principal, teachers, and students. The results indicate that the implementation of transformational leadership at MTs Muhammadiyah Tanjung Ampalu has had a positive impact on character development, improving student discipline, motivation, and active participation in religious and social activities. Positive interactions between teachers and students, supported by inspiring leadership, create an environment conducive to the moral and spiritual development of students. Thus, this study emphasizes that transformational leadership plays a crucial role in improving the quality of education and the character development of students in Islamic schools.